Identifikasi Pemporosan pada Lini Proses Logistik Hotel PYX dengan Value Stream Mapping - I Gusti Agung Mas Putri Anggita; I Made Dwi Budiana Penindra; I Gusti Agung Gangga Tirtayasa (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2026)
This study aims to identify and minimize waste in the process of procuring Food & Beverage raw materials at Hotel PXY Jasa Bali using the Lean Inventory Management approach. Observations over one month showed that the total procurement cost reached 47% of the total revenue, exceeding the ideal limit of 35%. One of the main causes is the inefficient and lack of synchronization between divisions in the Rhapsody platform, which causes waste in the form of defects, delays, over-processing, and transportation. This study uses the Value Stream Mapping (VSM) method to map actual conditions and Process Activity Mapping (PAM) to identify the type of activity based on the waste category. In addition, root cause analysis is carried out using the Root Cause Analysis (RCA) approach. The mapping results showed that out of the total lead time of 598.44 minutes, only 278.49 minutes or 46.54% were value-added activities. This finding indicates that the procurement process is not yet efficient and needs optimization. Several recommendations were given to minimize waste, such as clearer division of tasks, improved communication with vendors, and the procurement of supporting facilities to reduce physical movement between divisions. The implementation of this lean service is expected to be able to increase the efficiency of the logistics process and reduce the company's overall operational costs.